Implementasi metode role playing dalam menumbuhkan sikap berbakti siswa kepada orang tua pada mata pelajaran akidah akhlak di MI Hidaytul Mubtadi'in Cibentang - Siti Luluah Muayadah; Nia Yulianti; Elza Hudzahifahizza Saba Bila; Mafruhatun Ni’mah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
ABSTRACT This study was motivated by the low implementation of filial attitudes toward parents among students, although the material has been taught in Akidah Akhlak learning. Learning activities that are still dominated by the lecture method cause students to lack meaningful and applicable learning experiences. This study aims to identify the implementation of the role playing method, its role in fostering students’ filial attitudes toward parents, as well as the supporting and inhibiting factors in its application in Akidah Akhlak learning at MI Hidayatul Mubtadi’in Cibentang. This research employed a qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The results showed that the implementation of the role playing method was carried out through structured stages of planning, implementation, and evaluation. This method was able to improve students’ participation, empathy, confidence, and understanding of the importance of respecting and obeying parents. Supporting factors included students’ enthusiasm, teacher creativity, and a religious school environment, while the inhibiting factors were limited learning time and the low self-confidence of some students. This study indicates that the role playing method is effective in Akidah Akhlak learning to strengthen students’ character formation at the madrasah ibtidaiyah level. Keywords Role Playing; Akidah Akhlak; Devotion to Parents; Student Character; Madrasah Ibtidaiyah ABSTRACT Penelitian ini dilatarbelakangi oleh rendahnya implementasi nilai berbakti kepada orang tua dalam perilaku siswa meskipun materi tersebut telah diajarkan dalam pembelajran Akidah Akhlak. Proses pembelajaran yang masih didominasi metode ceramah menyebabkan siswa kurang memperoleh pengalaman belajar yang bermakna dan aplikatif. Penelitian ini bertujuan untuk mengetahui implementasi metode role playing, peran metode role playing dalam menumbuhkan sikap berbakti siswa kepada orang tua, serta faktor pendukung dan penghambat dalam penerapannya pada mata pelajaran Akidah Akhlak di MI Hidayatul mubtadi’in Cibentang. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa penerapan metode role playing dilakukan melalui tahap perencanaan, pelaksanaan, dan evaluasi pembelajaran yang terstruktur. Metode ini mampu meningkatkan partisipasi, empati, keberanian, serta pemahaman siswa terhadap pentingnya menghormati dan menaati orang tua. Faktor pendukung penelitian meliputi antusiasme siswa, kreativitas guru, dan lingkungan madrasah yang religius, sedangkan faktor penghambatnya berupa keterbatasan waktu pembelajaran dan rendahnya rasa percaya diri sebagian siswa. Penelitian ini menunjukan bahwa metode role playing memberikan kontribusi positif dalam pembelajaran Akidah Akhlak untuk memperkuat pembentukan karakter siswa tingkat Madrasah Ibtidaiyah. Kata Kunci: Role Playing; Akidah Akhlak; Berbakti kepada Orang Tua; Karakter Siswa; Madrasah Ibtidaiyah. This is an open-access article under the CC–BY-SA license.